Back Cover: Phenol‐Substituted Tetrapyrazinoporphyrazines: pH‐Dependent Fluorescence in Basic Media (Chem. Eur. J. 41/2015). Issue 41 (23rd September 2015) - Novakova, Veronika; Lásková, Miroslava; Vavřičková, Hana; Zimcik, Petr
<x xml:space="preserve">Abstract</x> OFF‐ON‐OFF switching of red fluorescence is demonstrated by V. Novakova, P. Zimcik et al. in their Full Paper on page 14382 ff., on phenol‐bearing metal‐free tetrapyrazinoporphyrazines in basic media. These molecules are nonfluorescent in neutral state, and they turn ON upon addition of a small amount of base due to deprotonation of central NH groups. A larger amount of base deprotonates the phenol moieties on the periphery and turns the molecules back to the OFF state due to intramolecular charge transfer from phenolate to the macrocycle.